Air pollution and economic sanctions in Iran - Hamid Balali; Mohammad Reza Farzanegan; Omid Zamani; Mostafa Baniasadi (Philipps-University Marburg, School of Business and Economics, 2023)
This study aims to simulate the future trends of carbon emissions under different international sanction scenarios in Iran. A System Dynamics (SD) model is developed and several variables that capture multiple levels of economic, social, and environmental concepts are taken into account. Our findings indicate that, despite Iran's sluggish economic growth, fossil fuel use and CO2 emissions will rise in the scenarios with international sanctions. Imposed sanctions on Iran exacerbate the environmental negative externalities through increasing energy intensity of economic sectors and consequently cause more CO2 emissions. Thus, based on our findings, prolonging international sanctions could be a major barrier to improving energy intensity and lowering CO2 emissions. Given the potential unintended environmental consequences of international sanctions, this study suggests that international communities, particularly sanctioning countries, should consider the environmental impacts of sanctions in their policy-making decisions in order to reduce emissions and related environmental damages.
Keywords: P18; F51; Q2; 330; Sanctions; System Dynamics; Environmental Impacts; Simulation; CO2 Emissions; Iran; JCPOA